Анализ возможностей существующих программных средств для проведения виртуального планирования хирургических вмешательств на внутреннем ухе человека - Бых, А. И.; Евстратов, Н. Д.; Пащенко, А. А. (Інститут електродинаміки НАНУ, 2011)
The main purpose of this work is to determine the sequence of surgical planning procedures and review the software, which allow executing all this actions. The possible application of 3D Slicer and Visual Ear Simulator in surgical planning routine are shown. Given the conclusions of this applications usage possibility in surgical planning.
Keywords: surgical planning; inner ear; surgical simulation; CT; MRT